Profitability as a factor of antecedent - Siti Epa Hardiyanti; Akhmadi (PT Larva Wijaya Penerbit, 2022)
The research aims to examine profitability as an antecedent factor in the influence of size and growth on firm value. The population in this study, namely the financial institutions sub-sector companies listed on the Indonesia Stock Exchange in 2013-2017 amounted to 17 companies. While the research sample used 12 companies. The analysis technique uses descriptive statistics and inferential statistics which included classical assumption test, multivariate regression, hypothesis test and antecedent test. The results showed that size has a positive and insignificant effect on profitability, growth has an insignificant negative effect on profitability, profitability has a non-significant positive effect on firm value, and profitability was an antecedent factor in the influence of size and growth on firm value.